The Feminization of the Corporation, the Masculinization of the State - Hallsworth, Simon (Social justice, 2005)
Part of a special issue on emerging imaginaries of regulation, control, and repression. The writer indicates that the response by men to the challenge posed by feminism has been to espouse forms of social control that apparently appropriate aspects of an effeminized culture or to engage in forms of control that mark a stark rejection of everything that can be construed as feminine. He discusses these contradictory movements by examining how the corporate sector and the state in Anglo-American societies have responded to qualities and values the Western gendered order has historically imputed to the feminine. He contends that corporate effeminization is a marketing ploy that permits corporations to deny the central masculinist traits that really motivate them and appear to have embraced a cultural order in which gender is on the move; whereas the state's war on crime lacks even a hint of progressive engagement with feminism.